The Effectiveness of the Ecological ICMS from the Perspective of a Public Environmental Policy: The Case of the Water Conservative Project in Extrema/MG (Research, Society and Development, 2022)
The Conservation Units refer to one of the environmental subcriteria of Minas Gerais State Law No. 18030/2009, which regulates the transfer rules regarding the tax on the circulation of goods and services - ICMS for the municipalities. In this sense, the objectives of the present research are to understand the transfer of ecological ICMS by the state of Minas Gerais, through Conservation Units, to identify the evolution of the number of Minas Gerais municipalities able to receive this tax and to analyze the effectiveness of public environmental policy Extrema / MG, in relation to the ecological ICMS and its Conservation Units. The research was based on bibliographical surveys, document analysis, with exploratory purpose and quantitative and qualitative approach, where a case study was carried out, limited to the Extrema/MG Conservative Water project. The results showed that the number of Minas Gerais municipalities that are entitled to the ecological ICMS is growing and that the Conservative Water project in Extrema / MG has the potential to impact the receipt of this tax. Finally, it was found that the ecological ICMS is influencing Minas Gerais municipalities to good environmental practices; that the Conservative Water project through the Conservation Units can impact on the increase of the ecological ICMS in Extrema / MG and that the research will promote the knowledge of municipalities about the methodology used by the “Robin Hood” law for the distribution of ecological ICMS.